Ageing and the welfare state: securing sustainability - Meier, Volker; Werding, Martin (Munich, 2010)
"Over the next four decades, increasing old-age dependency ratios exert an enormous upward pressure on welfare spending in most developed countries. As this is mainly due to existing unfunded public pension schemes, many countries have embarked on far-reaching reforms in this area, strengthening actuarial fairness, modifying indexation rules, adding elements of prefunding and, last but not least, attempting to extend the period of economic activity. Efforts to contain costs may also be relevant with regard to public expenditure on health and long-term care but, thus far, no country has started to really deal with these issues. Still, some countries have made substantial progress in securing the long-term sustainability of their welfare systems. What remains to be considered is re-constructing the system of intergenerational transactions as a potential way of removing disincentives to raise children and invest in their human capital in the long run. "